Integrated exposure for risk assessment in indoor environments based on a review of concentration data on airborne chemical pollutants in domestic environments in Europe. Issue 8 (December 2015) - Karakitsios, S.; Asikainen, A.; Garden, C.; Semple, S.; Brouwere, K. De; Galea, K. S.; Sánchez-Jiménez, A.; Gotti, A.; Jantunen, M.; Sarigiannis, D.
This review set out to identify data sets for airborne chemical pollutants measured in domestic dwellings within European Union (EU) countries from the literature published during 1995–2010. A total of 74 papers satisfied inclusion criteria, and from those papers data on country location, population sampled, sampling period, number of samples and summary statistics of concentrations measured were gathered. The chemical substances identified and included were grouped to aldehydes, radon, carbon dioxide (CO2 ), carbon monoxide (CO), nicotine, nitrogen dioxide (NO2 ), polycyclic aromatic hydrocarbons, volatile organic compounds and brominated flame retardants. The review showed that the availability of data between the EU countries is varying and more measured data are available for countries in northern Europe than in the southern parts. This review is part of the Integrated Exposure for Risk Assessment in Indoor Environments project which developed a full-chain modelling platform, incorporating tools and databases for indoor chemical source release, exposure and risk assessment with the ultimate aim of estimating the health impact of chemical exposures in the indoor environment.